Your work wellness toolkit : mindset tips, journaling and rituals to help you thrive - Bard, Ellen M. (Watkins, 2022)
"An interactive journal showing the reader how to feel better at work, be more productive, more positive, more resilient. The book is illustrated throughout with interactive activities, journal prompts and a structured programme of self-care for the workplace. Burnout is described by the WHO as: feelings of energy depletion or exhaustion; increased mental distance from your job, or feelings of negativism or cynicism related to your job; reduced professional efficacy. All of these things can be prevented with conscious attention to creating better workplace habits, rituals and routines. Your Work Wellness Toolkit will present guidance to curate your own wellness plan to thrive at work. Too many of us are struggling with managing the mental health load of working remotely, and boundaries between work and life are more blurred than ever before. This book not only offers thorough and clinically backed-up guidance, but also space to make plans and accountability within that guidance, to put it into action." -- Amazon.com.